Sosialisasi Pemahaman Perjalanan Penyakit Untuk Meningkatkan Kesadaran Kesehatan Masyarakat - Riasari Mardani; Fathul Azmi; Dhandi Hidayatullah; Muhammad Atta Iqbal; Hartiani (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
Non-communicable diseases have become a global health threat with increasing prevalence in Indonesia, particularly in regions experiencing lifestyle transitions. Community understanding of disease progression serves as a crucial foundation in empowering individuals for responsible health decision-making. This study aimed to analyze the effectiveness of disease journey understanding socialization programs in enhancing health awareness among Aikmel community. The research employed a cross-sectional design with quantitative approach involving 38 adult respondents aged 25-60 years selected through purposive sampling. Data collection was conducted through validated questionnaires with pretest and posttest measurements to evaluate knowledge levels, attitudes, and health behavior intentions. Data analysis utilized paired t-test and Wilcoxon signed-rank test with significance level of p<0.05. Research findings demonstrated significant increases in knowledge scores from 11.8±3.2 to 16.7±2.4 (41.5% increase), attitude scores from 48.6±8.4 to 62.8±6.7 (29.2% increase), and behavioral intentions from 21.1-39.5% to 73.7-86.8% across various preventive health behavior domains. The program successfully identified 16 new cases of chronic diseases through enhanced early detection practices. This study concludes that disease journey understanding socialization effectively improves community health literacy and can serve as a community-based intervention strategy for non-communicable disease prevention.